The Use of Cognate Cosolvent to Mediate Localized High-Concentration Electrolytes for High-Voltage and Long-Cycling Lithium-Metal Batteries - Ying Hu; Dandan Wang; Qijie Yu; Ziyi He; Fengrui Deng; Hao Yan; Tinglu Song; Jin-Cheng Zheng; Yang Dai (Batteries)
Localized high-concentration electrolytes (LHCEs) are promising systems for improving the high-voltage performance and interfacial stability of lithium-metal batteries (LMBs). Unfortunately, they are always challenged by liquid–liquid phase separation during solution preparation. Further investigation is always required when the prepared electrolyte has encountered liquid–liquid phase separation previously. Here, we propose a “cognate cosolvent” strategy to mediate phase-separated LiBF4/fluoroethylene carbonate (FEC)|ethyl trifluoroacetate (TFAE) mixtures with ethyl acetate (EA), forming effective LiBF4/FEC/EA/TFAE-based LHCEs (B-LHCEs). Because of their unique solvation structure, the B-LHCEs exhibit high oxidative stability, facilitating Li+ transport. The optimized B-LHCEs help single-crystal LiMn0.8Mn0.1Co0.1O2/Li batteries form robust interphases, improving interfacial stability. As a result, distinct performance can be obtained (4.5 V, 500 cycles, ~90%, 1400, ~70%; 25 C, 128 mAh g−1, 4.7 V, 500, 82.5%). This work turns the “impossible” into an “effective” high-voltage electrolyte design, transcending the previous paradigms of electrolyte investigation and enriching LHCE preparation research.